'A solid foundation for a career in indexing': the story of the Society of Indexers' training course. (1st December 2020) - Hudson, Ann
Abstract : With the publication in 2020 of the fifth edition of the Society of Indexers' training course, the current Training Director traces the development of training in the Society of Indexers (SI) since its foundation in 1957. From lectures held in London, through a paper-based course relying on the postal service, to a modern online course using digital technology to deliver a more immediate and personalized experience, indexing training has been through many transformations. Throughout, an emphasis on rigour and the maintenance of standards has been paramount.